A systematic review of antibacterial activity of polyphenolic extract from date palm (Phoenix dactylifera L.) kernel - Bhaskaracharya, Raman K.; Bhaskaracharya, Archana; Stathopoulos, Constantinos (Frontiers in Pharmacology, 2023)
Background: Emergence of antibiotic-resistant bacteria makes exploration of natural antibacterial products imperative. Like other fruit processing industry by-products, date kernels, a waste from date processing industry is rich in its extractable polyphenols. The rich polyphenolic content suggests that date kernel extracts (DKE) can be a cost-effective source of antimicrobial agents, however, their antibacterial activity is poorly understood. Hence, a systematic review of available literature to establish DKE’s antibacterial activity is warranted. Methods: A systematic PRISMA approach was employed, and relevant studies were identified using defined keywords from Google Scholar, Scopus, PubMed, and Web of Science databases. The search results were screened based on predefined eligibility criteria and data extraction, organization, pooling, and descriptive statistical analyses of original research records conducted. Results: A total of 888 published records were retrieved from databases. Preliminary screening by applying specific eligibility criteria reduced records to 96 which after full text screening further decreased to 14 records. Escherichia coli and Staphylococcus aureus were the most studied organisms. Results indicate moderate to highly active effect shown by the less polar solvent based DKE’s against gram-positive and by the aqueous based DKE’s against gram-negative bacteria. The review confirms antibacterial activity of DKE against both gram-positive and -negative bacteria. Heterogeneity in reported polyphenolic content and antibacterial activity are due to differences in cultivars, extraction methods, test methods, model organisms, etc. Use of standardized protocols for isolation, characterization, testing of DKE’s active polyphenols to elucidate its antibacterial activity is recommended to establish the clinical efficacy of natural antibacterial compounds from DKE. Conclusion: This review outlines the current knowledge regarding antibacterial activity of polyphenolic DKE, identifying gaps in information and provides key recommendations for future research directions.